High-Entropy Layered Oxide Cathode Enabling High-Rate for Solid-State Sodium-Ion Batteries - Cai, Tianxun; Cai, Mingzhi; Mu, Jinxiao; Zhao, Siwei; Bi, Hui; Zhao, Wei; Dong, Wujie; Huang, Fuqiang (Nano-Micro Letters, 2023)
Na-ion O3-type layered oxides are prospective cathodes for Na-ion batteries due to high energy density and low-cost. Nevertheless, such cathodes usually suffer from phase transitions, sluggish kinetics and air instability, making it difficult to achieve high performance solid-state sodium-ion batteries. Herein, the high-entropy design and Li doping strategy alleviate lattice stress and enhance ionic conductivity, achieving high-rate performance, air stability and electrochemically thermal stability for Na0.95Li0.06Ni0.25Cu0.05Fe0.15Mn0.49O2. This cathode delivers a high reversible capacity (141 mAh g−1 at 0.2C), excellent rate capability (111 mAh g−1 at 8C, 85 mAh g−1 even at 20C), and long-term stability (over 85% capacity retention after 1000 cycles), which is attributed to a rapid and reversible O3–P3 phase transition in regions of low voltage and suppresses phase transition. Moreover, the compound remains unchanged over seven days and keeps thermal stability until 279 ℃. Remarkably, the polymer solid-state sodium battery assembled by this cathode provides a capacity of 92 mAh g−1 at 5C and keeps retention of 96% after 400 cycles. This strategy inspires more rational designs and could be applied to a series of O3 cathodes to improve the performance of solid-state Na-ion batteries. Highlights: 1 High-entropy oxides O3-Na0.95Li0.06Ni0.25Cu0.05Fe0.15Mn0.49O2 cathode constructed by compatible radius and different Fermi level ions was designed for solid-state Na-ion batteries. 2 Na0.95Li0.06Ni0.25Cu0.05Fe0.15Mn0.49O2 cathode exhibits high-rate performance, air stability and electrochemically thermal stability. 3 A series of characterizations were performed to explore energy storage mechanism of Na0.95Li0.06Ni0.25Cu0.05Fe0.15Mn0.49O2.